AB0045 Baff signaling pathway may be involved in the production of matrix metalloproteinase-9 by peripheral monocytes of patients with primary sjögren's syndrome. (23rd January 2014) - Yoshimoto, K.; Tanaka, M.; Kojima, M.; Ogata, H.; Suzuki, K.; Kameda, H.; Abe, T.; Takeuchi, T.
Abstract : Background: B cell activating factor of the TNF family (BAFF) is a type II membrane-bound protein and the extracellular C-terminal fragment is released from the cells as soluble BAFF (sBAFF). BAFF is mainly produced by monocytes and dendritic cells, and regulates proliferation, differentiation, and survival of B cells. In our previous study, we found that the production of IL-6 was significantly enhanced in monocytes of primary Sjögren's syndrome (pSS) upon stimulation with sBAFF. We also found that the expression level of a BAFF receptor (BR3) was significantly elevated in pSS monocytes compared to normal monocytes. These data suggest that the elevated expression of BR3 on monocytes is involved in the abnormal production of IL-6 by pSS monocytes. In this study, we explored other abnormalities of pSS monocytes. We especially focused on matrix metalloproteinases (MMPs), because MMPs were reported to be involved in the pathogenesis of autoimmune diseases. Objectives: To purpose of this study is to elucidate that elevated expression of BR3 on monocytes is involved in the abnormal production of matrix metalloproteinase-9. Methods: The expression levels of BR3 and MMPs in monocytes in whole blood samples of pSS patients (n = 19) and age matched normal individuals (n = 14) were analyzed by PCR and FACS. Signal transduction pathways were investigated by exposing sBAFF-stimulated pSS monocytes to several inhibitors against possible downstream targets. Results: RT-PCR analysis detected the expression of MMP-2 and 9 in peripheral monocytes of both pSS patients and normal individuals. Stimulation of the cells with sBAFF enhanced the expression of the latter. ELISA showed robust enhancement of the production of MMP-9 by pSS monocytes compared to the control. The amount of MMP-9 produced by the cells was positively correlated with the expression level of BR3, suggesting that BAFF-signaling is important for the production of MMP-9 by pSS monocytes. Moreover, the elevated productions of MMP-9 by the cells were significantly suppressed by specific inhibitors against NF-kB and PI3 kinase in a dose dependent manner. Conclusions: The present study suggests that sBAFF acts through BR3 to activate the expression of MMP-9, and that NF-kB and PI3 kinase are involved in the signal transduction pathway. References: Yoshimoto K, Tanaka M, Kojima M, Setoyama Y, Kameda H, Suzuki K, Tsuzaka K, Ogawa Y, Tsubota K, Abe T, Takeuchi T. Regulatory mechanisms for the production of BAFF and IL-6 are impaired in monocytes of patients of primary Sjögren's syndrome. Arthritis Res Ther. 2011;13(5):R170. Epub 2011 Oct 21 Disclosure of Interest: None Declared